SUBSTRATE PREFERENCE AMONG GASTROPOD SPECIES IN A POND IN THE ARID REGION OF RAJASTHAN - SINGH, YOGENDER; SAXENA, M. M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
Substrate preference among four gastropod species namely Digoniostoma pulchella, Gabbia orcula, Indoplanorbis exustus and Gyraulus rotula was studied in freshwater pond in the Indian desert as well as under laboratory conditions. Prosobranch snails D. pulchella preferred pond mud while G orcula floated close to surface. Pulmonate G. rotula remained associated with Hydrilla while I exustus preferred pond pebble though it harboured almost any kind of available substrate.